Gender Differences in Metabolic Disorders and Related Diseases in Spontaneously Diabetic Torii-Leprfa Rats - Takeshi Ohta; Yoshiaki Katsuda; Katsuhiro Miyajima; Tomohiko Sasase; Shuichi Kimura; Bin Tong; Takahisa Yamada (Journal of Diabetes Research)
The Spontaneously Diabetic Torii Leprfa (SDT fatty) rat is a novel type 2 diabetic model wherein both male and female rats develop glucose and lipid abnormalities from a young age. In this study, we investigated gender differences in abnormalities and related complications in SDT fatty rats. Food intake was higher in males compared to female rats; however, body weight was not different between genders. Progression of diabetes, including increases in blood glucose and declines in blood insulin, was observed earlier in male rats than in females, and diabetic grade was more critical in male rats. Blood lipids tended to increase in female rats. Gonadal dysfunction was observed in both male and female rats with aging. Microangiopathies, such as nephropathy, retinopathy, neuropathy, and osteoporosis, were seen in both genders, and pathological grade and progression were more significant in males. Qualitative and quantitative changes were observed for metabolic disease gender differences in SDT fatty rats. The SDT fatty rat is a useful model for researching gender differences in metabolic disorders and related diseases in diabetes with obesity.